The effect of river-based lessons on middle school students` awareness of drowning prevention - Inagaki, R.; Watanabe, Y.; Kishi, T.; Hasegawa, K. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Drowning prevention is a global issue. The United Nations designated July 25th as World Drowning Prevention Day starting from 2021 (Uinted Nations, 2021). In Japan, 13,808 people were involved in water-related accidents over the 10-year period from 1 April 2013 to 31 March 2022, of which 7,409 people died or are still missing. The number of children aged 15 and under who died or went missing was 346, and these cases are distributed as follows: 183 (52.9%) in rivers, 75 (21.7%) in the sea, 40 (11.6%) in lakes, ponds, and swamps, 32 (9.2%) in irrigation channels, and 11 (3.2%) in pools (National Police Agency, 2023). This clearly indicates that incidents occur much more frequently in natural aquatic environments compared to pools. Furthermore, when categorizing the deaths and missing children by activity, 161 cases (46.5%) were related to playing in the water, 44 cases (12.7%) to swimming, 25 cases (7.2%) to fishing or catching fish, and 20 cases (5.8%) to passing by water (National Police Agency, 2018, 2023). This indicates that in order to prevent drowning incidents among children, it is necessary to consider educational content that takes these activities into account. In Japan, efforts to enhance children's crisis management abilities have emphasized the cultivation of effective skills after falling into water. Methods such as maintaining a supine position to ensure breathing and waiting for rescue, as well as using items like plastic bottles or bags to aid buoyancy, are actively taught in elementary and middle schools. However, Stallman et al. (2017) propose that drowning prevention education for children should incorporate risk awareness and risk avoidance behaviors related to drowning prevention. They suggest including natural environments such as beaches, rivers, and lakes in the educational programs. In the context of Japan's school education, fostering not only children's crisis management skills but also their risk management skills appears to be an urgent task. To achieve this, exploring learners' awareness, emotions, knowledge, and attitudes would serve as a starting point. The aim of this study is to elucidate the impact and sustainability of river-based lessons on the emotions and awareness of middle school students regarding drowning prevention. The study also examined participants' knowledge and attitudes concerning drowning incidents.